Discourse analysis from an international relations perspective: the case study of Tucker Carlson’s televised interview with Vladimir Putin - Pablo Hidalgo-Cobo; Casandra López-Marcos; Belén Puebla-Martínez (AD Research)
Objective: This research examines Putin’s discourse in the Tucker Carlson interview of 6 February 2024 through the lens of international relations theories. The objective is to identify the main topics, themes and arguments put forward by the Russian president in a political discourse within the context of a war.